Palynostratigraphy, Palynofacies, T-R Cycles and Paleoenvironments in the Middle Jurassic–Early Cretaceous Ramså Basin, Andøya, Northern Norway - Morten Smelror (Geosciences, 2021)
Palynostratigraphy and palynofacies analyses are applied to identify transgressive-regressive sequences and changes in paleoenvironment through the Middle Jurassic–Early Cretaceous succession of the Ramså Basin on Andøya. The conglomerate, the succeeding lacustrine-swamp deposits of the Hestberget and Kullgrøfta members (Ramså Formation) and the overlying terrestrial to marginal marine deposits of the lower Bonteigen Member (Ramså Formation), comprise the Bajocian T-R sequence. Bathonian–Oxfordian strata appear to be missing in the studied boreholes, and the second T-R cycle spans the Kimmeridgian to Berriasian open marine deposits of the upper Bonteigen Member and the Dragneset Formation (Breisanden, Taumhølet and Ratjønna members). The overlying Nybrua Formation comprises a condensed marine succession of Valanginian–Early Barremian calcareous sandstone and marl, followed by brownish-red siltstone. The upper T-R sequence (Skarstein Formation) consists of marine transgressive Barremian dark siltstones, silty shales and mudstones, followed by dark mudstone and shale. Marine palynomorphs recovered in these stacked marine slope turbidite sediments are of Late Barremian age, but possibly the youngest T-R cycle also includes Aptian deposits elsewhere in the basin.